2020
DOI: 10.1002/aepp.13083
|View full text |Cite
|
Sign up to set email alerts
|

Does Trade Policy Uncertainty Affect Agriculture?

Abstract: This article reviews evidence of trade war impacts and emerging concerns on trade policy uncertainty. Trade war's near-perfect pass-through of tariffs to US prices favored producers and generated government revenue at the expense of consumers. Facing retaliation, prices and trade volumes were found to be lower for US agricultural commodities. The recent rethink on the benefits of globalization by major economies has led to uncertain policy paths wherein firms and consumers continue to make decisions. Using qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The results also show that perceived policy uncertainty may cause dairy farmers to postpone investments. A similar result was found by Gopinath (2021) who found that higher trade policy uncertainty relates to significantly lower gross farm investment. Their results suggest that farmers may postpone their investments when trade policy uncertainty is higher.…”
Section: Discussionsupporting
confidence: 86%
“…The results also show that perceived policy uncertainty may cause dairy farmers to postpone investments. A similar result was found by Gopinath (2021) who found that higher trade policy uncertainty relates to significantly lower gross farm investment. Their results suggest that farmers may postpone their investments when trade policy uncertainty is higher.…”
Section: Discussionsupporting
confidence: 86%
“…In line with this, Chapter 3 found that the anticipating strategy, i.e., investing early, is more attractive to farmers who perceive less policy uncertainty. This finding is in line with Gopinath (2021), who found that farmers invest less in years with higher policy uncertainty. Similarly, Gatzert and Vogl (2016) found that including policy uncertainty has a strong effect on the present value of cash flows of investments, showing that higher policy uncertainty makes investing less interesting.…”
Section: The Relation Between Policy Uncertainty and Decision Makingsupporting
confidence: 91%
“…While this could be due to a combination of the tariff and coronavirus disease 2019 pandemic, given the strict lockdown policies in China (Pei et al, 2022), Bown (2022) notes that the pandemic had the direct opposite effect on imports from China not subject to tariffs (e.g., video games). Given the increase in imports from other countries during this period, this could also reflect the uncertainty and political tensions between the two countries (Gopinath, 2021).…”
Section: Resultsmentioning
confidence: 99%